Kinase Targets for Mycolic Acid Biosynthesis in Mycobacterium tuberculosis. - Alsayed, S.; Beh, C.; Foster, Neil; Payne, A.; Yu, Y.; Gunosewoyo, H. (2018)
Mycolic acids (MAs) are the characteristic, integral building blocks for the mycomembrane belonging to the insidious bacterial pathogen Mycobacterium tuberculosis (M.tb). These C60-C90 long a-alkyl-ß-hydroxylated fatty acids provide protection to the tubercule bacilli against the outside threats, thus allowing its survival, virulence and resistance to the current antibacterial agents. In the post-genomic era, progress has been made towards understanding the crucial enzymatic machineries involved in the biosynthesis of MAs in M.tb in which two discrete fatty acid synthases systems (FAS-I and FAS-II) were discovered. However, gaps still remain in the exact role of the phosphorylation and dephosphorylation regulatory mechanisms within these systems. To date, a total of 11 serine-threonine protein kinases (STPKs) are found in M.tb. Most enzymes implicated in the MAs synthesis were found to be phosphorylated in vitro and/or in vivo. For instance, phosphorylation of KasA, KasB, mtFabH, HadAB/BC, InhA, MabA, FadD32 and PcA downregulated their enzymatic activity, while phosphorylation of VirS increased its enzymatic activity. These observations suggest that the kinases and phosphatases system could play a role in M.tb adaptive responses and survival mechanisms in the human host. As the mycobacterial STPKs do not share a high sequence homology to the human's, there has been some early drug discovery efforts towards developing potent and selective inhibitors as novel antitubercular agents. Recent updates to the kinases and phosphatases involved in the regulation of MAs biosynthesis will be presented in this minireview, including their known small molecule inhibitors.